Neural correlates of concreteness effect in semantic processing of single Chinese characters using mixed-effects modeling. (November 2017) - Law, Sam-Po; Yum, Yen-Na; Wing-Lam Cheung, Gervais
Abstract: This study examined the ERP correlates of concreteness effects on single Chinese characters of different form classes, including nouns, verbs and adjectives, in a go/no-go semantic categorization task. Diverging from previous works, the current study employed a non-factorial design and focused on semantic processing of single characters representing a spectrum of concreteness values to ensure high ecological validity. The results of linear mixed-effects modeling showed that concreteness modulated N400 amplitudes elicited by monomorphemic nouns and verbs in posterior regions, similar to previous studies examining compound words. Concreteness continued to modulate neural response to verbs in the same pattern as in the N400 during 500–1000 ms. The absence of a sustained frontal negativity was proposed to be due to the use of single character stimuli and a lack of explicit contrast in concreteness across stimuli that did not encourage imagery processing. The opposite forms of manifestation of the concreteness effects on the two major form classes were attributed to task requirements. Highlights: This ERP study examined concreteness effects on single Chinese characters. It employed a non-factorial design using linear mixed-effects modeling. Concreteness modulated N400 amplitudes of nouns and verbs in posterior regions. Single morphemes varying in concreteness did not elicit a frontal negativity.